Pliocene bats (Chiroptera) from Kanapoi, Turkana Basin, Kenya. Issue 140 (March 2020) - Gunnell, Gregg F.; Manthi, Fredrick K.
Abstract: Fossil bats from the Pliocene of Africa are extremely rare, especially in East Africa where meager records have been reported only from two localities in the Omo River Basin Shungura Formation and from a scattering of localities in the Afar Depression, both in Ethiopia. Here we report on a diverse assemblage of bats from Kanapoi in the Turkana Basin that date to approximately 4.19 million years ago. The Kanapoi bat community consists of four different species of fruit bats including a new genus and two new species as well as five species of echolocating bats, the most common of which are two new species of the molossid genus Mops . Additionally, among the echolocating bats, a new species of the emballonurid Saccolaimus is documented at Kanapoi along with an additional Saccolaimus species and a potentially new species of the nycterid Nycteris . Compared to other East African Pliocene bat assemblages, the Kanapoi bat community is unique in preserving molossids and curiously lacks any evidence of cave dwelling bats like rhinolophids or hipposiderids, which are both common at other East African sites. The bats making up the Kanapoi community all typically roost in trees, with some preferring deeper forests and larger trees (molossids), while the others (pteropodids, nycterids and emballonurids) roost in trees near open areas. Living fruit bats that are related to Kanapoi species typically forage for fruits along the margins of forests and in open savannah. The echolocating forms from Kanapoi consist of groups that aerially hawk for insects in open areas between patches of forest and along water courses. The habitats preferred by living relatives of the Kanapoi bats are in agreement with those constructed for Kanapoi based on other lines of evidence.